2021
DOI: 10.1002/adem.202001475
|View full text |Cite
|
Sign up to set email alerts
|

High‐Quality Translucent Alumina Ceramic Through Digital Light Processing Stereolithography Method

Abstract: Herein, translucent alumina ceramics with fine complex geometric shapes are successfully fabricated by a digital light processing (DLP) process followed by vacuum sintering. The interlayer bonding condition is the key for preparing highquality translucent alumina for this layer-by-layer additive manufacturing (AM) method. The curing characteristics of alumina suspensions are carefully investigated by curing depth and polymerization conversion behavior. It is clear that the residual stress resulted from the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Sun et al reported obtaining translucent alumina using DLP using a particle size of ∼400 nm and vacuum sintering with MgAl 2 O 4 as the sintering additive. 37 They achieved a 55 vol % solids loading.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sun et al reported obtaining translucent alumina using DLP using a particle size of ∼400 nm and vacuum sintering with MgAl 2 O 4 as the sintering additive. 37 They achieved a 55 vol % solids loading.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Among oxide ceramics, lithography-based 3D-printing of alumina (Al 2 O 3 ) has been given particular attention given it desirable properties for structural, energy, and electronics applications. ,,, Chen et al reported that the viscosity of alumina slurries decreases as the fraction of fine powder (∼1.1 μm) to coarse powder (∼5.8 μm) increases, and the particle size distribution affects the curing behaviors slightly . Zhang et al achieved an alumina dispersion with 60 vol % and viscosity of ∼15 Pa s through the optimization of suspension parameters .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZrO 2 [276][277][278][279][280][281][282][283][284][285][286][287] [296] Heat exchanger/dissipation Al 2 O 3 [170], AlN [297][298][299] Tool with optimized design (inner cooling structure) Al 2 O 3 [180], cemented carbide [300] Optical application (lens, armored/ sensor window, etc.) Al 2 O 3 [301], MgAl 2 O 4 spinel [302], SiC [303], Nd-doped YAG [304], Yb-doped YAG [305] Antenna Al 2 O 3 +glass [306], Ba 1-x Sr x Zn 2 Si 2 O 7 [307], MgTiO 3 +CaTiO 3 [308] Nuclear fusion Li 2 TiO 3 [309], Li 2 SiO 3 [310] Table VIII waste. Thus, machines that work with a small amount of material (60 mL) [316] and studies about recycling raw materials [286,354] have emerged.…”
Section: Vat Photopolymerizationmentioning
confidence: 99%
“…In addition, we note another promising method—Stereolithography (or Vat photopolymerization) [ 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ]. The method of stereolithography is based on the layer-by-layer controlled polymerization of photosensitive monomers (or suspensions with ceramic powders) under light irradiation.…”
Section: Producing and Utilizing Of The Precursorsmentioning
confidence: 99%